EMPLOYEE PERFORMANCE ANALYSIS IN THE SERVICE EDUCATION AND CULTURE OF EAST BOLAANG MONGONDOW REGENCY - Mokosuli, Susvita; Pangkey , Itje; Mamonto , Fitri (Retorika: Jurnal Komunikasi, Sosial dan Ilmu Politik, 2025)
Employee performance that has been carried out in the past with satisfactory assessments is certainly able to be placed by the organization to have a good assessment for its employees, but it is necessary to instill awareness that what is obtained through satisfactory performance still needs to be improved. The assessment obtained becomes a reference and benchmark for success in the future, therefore performance becomes a necessity to encourage employees to master the tasks and functions assigned so that performance is increasingly better in presenting a figure who always protects, fosters, guides and directs to good things. ASN as an asset in achieving regional development must continue to be developed and improved which cannot be postponed because the era of competition continues to move forward. with the aim of describing and studying how well the performance of employees at the East Bolaang Mongondow Regency Education and Culture Office is seen from the aspects of effectiveness and efficiency, authority and responsibility, discipline and initiative aspects. According to Sugiono (2020) qualitative research is called a "naturalistic research method because the research is conducted in natural conditions". The selection of Qualitative Methodology was chosen by researchers to reveal and understand in depth things that are not yet known or are only slightly known, and also researchers want to be directly involved in collecting data for research. Employee performance reviewed from the aspects of effectiveness and efficiency in carrying out work can be concluded that employees work optimally in accordance with the applicable SOP in the Department of Education and Culture Where employees do their work optimally in accordance with the job description which is the responsibility of each employee, in terms of costs arising from the work of employees working optimally so that there is an effect of efficiency in budgeting expenditures arising from the work Where also the Department of Education and Culture is carrying out budget efficiency due to limited DPA funds from the Department of Education and Culture in supporting planned programs / activities. From the aspect of job suitability, competence and employee placement are considered appropriate even though there are still employees who do not have a Bachelor's degree.